2019
DOI: 10.17816/rcf1735-38
|View full text |Cite
|
Sign up to set email alerts
|

Eryptosis (quasi-apoptosis) the human red blood cells. Its role in medicinal therapy

Abstract: In the course of circulation erythrocytes can test damages, which compromises their integrity and thus triggers suicidal erythrocyte death or eryptosis. This mechanism is characterised by cell shrinkage, cell membrane blebbing, and cell membrane phospholipid scrambling after phosphatidylserine exposure on the cell surface that is identified by macrophages, which engulf and degrade the eryptotic cells. The term eryptosis also includes typical mechanisms, which contribute to the triggering of this process, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 278 publications
(420 reference statements)
0
1
0
1
Order By: Relevance
“…They can express caspase-3 and caspase-8 [ 53 ], but they do not display other elements of the apoptotic machinery, such as Apaf-1, cytochrome c , and caspases-2, -6, -7 and -9 [ 54 ]. Klatt et al (2018) reported that significant receptors belonging to the tumor necrosis factors (TNF) family (CD95 [ 55 ] and Fas [ 56 ]) signaling in RBCs are known to induce a particular type of programmed cell death, similar to the apoptotic death of nucleated cells named eryptosis [ 57 ], by caspase-3 activation, leading to cell shrinkage and cell membrane scrambling [ 58 ] with PS externalization [ 59 ]. The major trigger of eryptosis is the increase of cytosolic Ca 2+ activity resulting from Ca 2+ entry through Ca 2+ -permeable unselective cation channels (permeable to both Na + and Ca 2+ ) [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can express caspase-3 and caspase-8 [ 53 ], but they do not display other elements of the apoptotic machinery, such as Apaf-1, cytochrome c , and caspases-2, -6, -7 and -9 [ 54 ]. Klatt et al (2018) reported that significant receptors belonging to the tumor necrosis factors (TNF) family (CD95 [ 55 ] and Fas [ 56 ]) signaling in RBCs are known to induce a particular type of programmed cell death, similar to the apoptotic death of nucleated cells named eryptosis [ 57 ], by caspase-3 activation, leading to cell shrinkage and cell membrane scrambling [ 58 ] with PS externalization [ 59 ]. The major trigger of eryptosis is the increase of cytosolic Ca 2+ activity resulting from Ca 2+ entry through Ca 2+ -permeable unselective cation channels (permeable to both Na + and Ca 2+ ) [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…За своєю суттю підвищення АФК в еритроцитах призводить до ериптозу -процесу, що нагадує апоптоз ядровмісних клітин. Цей процес відбувається шляхом зморщування клітин, переміщення молекул фосфоліпідів з одного боку цитоплазматичної мембрани в інший, що призводить до зміни властивостей та функціональної активності еритроцитів [8]. Скремблювання фосфоліпідів клітинних мембран еритроцитів під час ериптозу зумовлює транслокацію фосфатидилсерину на зовнішній бік цитоплазматичної мембрани.…”
Section: обговоренняunclassified